Visual Simulation of Weathering By Î³-ton Tracing - Chen, Yanyun; Xia, Lin; Wong, Tien-Tsin; Tong, Xin; Bao, Hujun; Guo, Baining; Shum, Heung-Yeung (Association for Computing Machinery, Inc., 2005)
Weathering modeling introduces blemishes such as dirt, rust, cracks and scratches to virtual scenery. In this paper we present a visual simulation technique that works well for a wide variety of weathering phenomena. Our technique, called γ-ton tracing, is based on a type of aging-inducing particles called γ-tons. Modeling a weathering effect with γ-ton tracing involves tracing a large number of γ-tons through the scene in a way similar to photon tracing and then generating the weathering effect using the recorded γ-ton transport information. With this technique, we can produce weathering effects that are customized to the scene geometry and tailored to the weathering sources. Several effects that are challenging for existing techniques can be readily captured by γ-ton tracing. These include global transport effects, or “stain-bleeding”. γ-ton tracing also enables visual simulations of complex multi-weathering effects. Lastly, γ-ton tracing can generate weathering effects that not only involve texture changes but also large-scale geometry changes. We demonstrate our technique with a variety of examples.